Impact of Barrel Toasting on Ellagitannin Composition of Aged Cognac Eaux-de-Vie - Mathilde Gadrat; Catherine Emo; Joël Lavergne; Pierre-Louis Teissèdre; Kléopatra Chira (Molecules, 2022)
It is well established that C-glucosidic ellagitannins contribute to wine quality, and new forms of ellagitannins have been found recently in cognac eaux-de-vie. The contribution of some ellagitannin-derived spirit compounds to eaux-de-vie taste has been demonstrated recently. However, there is a gap in our knowledge of the content, composition, and evolution of C-glucosidic ellagitannins in this matrix. Indeed, the quantification of these compounds and their evolutionary compounds have never before been researched in cognac eaux-de-vie. Thus, the aim of this study was not only to quantify these compounds, but also to study their kinetics and to observe how they are impacted by barrel toasting. For this purpose, barrels representing eight different toasting levels were used to age the same eau-de-vie during the first 18 months. Ellagitannin quantification was carried out by HPLC-Triple quadrupole. The results showed that the evolutionary trend of the eight ellagitannins is the same for all eight types of barrel toasting. The maximum concentrations of C-glucosidic ellagitannins were found after 3 months of aging (up to 23 mg/L) before decreasing to 18 months (9.7 mg/L), whereas ellagitannin-derived spirit compound concentrations increased throughout aging (up to 130.9 mg/L). In addition, barrel toasting had such an impact on ellagitannin content that barrels could be differentiated according to their levels. Eaux-de-vie in barrels with high toasting were lower in ellagitannins concentrations.